Biochemical and genetic examination of two aminotransferases from the hyperthermophilic archaeon Thermococcus kodakarensis - Su, Yu; Michimori, Yuta; Atomi, Haruyuki (Frontiers in Microbiology, 2023)
The hyperthermophilic archaeon Thermococcus kodakarensis utilizes amino acids as a carbon and energy source. Multiple aminotransferases, along with glutamate dehydrogenase, are presumed to be involved in the catabolic conversion of amino acids. T. kodakarensis harbors multiple Class I aminotransferase homologs on its genome. Here we examined the biochemical properties and physiological roles of two Class I aminotransferases. The TK0548 protein was produced in Escherichia coli and the TK2268 protein in T. kodakarensis. Purified TK0548 protein preferred Phe, Trp, Tyr and His, and to a lower extent, Leu, Met and Glu. The TK2268 protein preferred Glu and Asp, with lower activities towards Cys, Leu, Ala, Met and Tyr. Both proteins recognized 2-oxoglutarate as the amino acceptor. The TK0548 protein exhibited the highest kcat/Km value towards Phe, followed by Trp, Tyr and His. The TK2268 protein exhibited highest kcat/Km values for Glu and Asp. The TK0548 and TK2268 genes were individually disrupted, and both disruption strains displayed a retardation in growth on a minimal amino acid medium, suggesting their involvement in amino acid metabolism. Activities in the cell-free extracts of the disruption strains and the host strain were examined. The results suggested that the TK0548 protein contributes to the conversion of Trp, Tyr and His, and the TK2268 protein to that of Asp and His. Although other aminotransferases seem to contribute to the transamination of Phe, Trp, Tyr, Asp and Glu, our results suggest that the TK0548 protein is responsible for the majority of aminotransferase activity towards His in T. kodakarensis. The genetic examination carried out in this study provides insight into the contributions of the two aminotransferases towards specific amino acids in vivo, an aspect which had not been thoroughly considered thus far.